THE QUR'AN'S PERSPECTIVE ON THE PROHIBITION OF CATCALLING: A HERMENEUTIC, GENDER, AND SOCIAL PSYCHOLOGY ANALYSIS - Hakim, M. Luqman; Fathoni, Ahmad Nur; Bahrudin, Moh.; Mukti, Anwar; Cahyono, Agung Mandiro; Azzahro, Ana Asyifa (West Science Islamic Studies, 2024)
Catcalling is a form of verbal sexual harassment that is often normalized in society, even though it has serious psychological impacts and reflects patriarchal power relations that are detrimental to women in public spaces. This study aims to analyze the prohibition of catcalling from the perspective of the Qur'an using hermeneutics, gender, and social psychology approaches. Through Qur'anic hermeneutics, verses such as QS. Al-Ahzab: 58, QS. An-Nur: 30–31, QS. Al-Hujurat: 11, QS. An-Nisa’: 148, and QS. Al-Isra’: 53 are interpreted as universal prohibitions against harassment, abusive language, and actions that demean human dignity. Gender analysis shows that catcalling is a social construct rooted in the patriarchal system, the objectification of women's bodies, and hegemonic masculinity. Meanwhile, social psychology reveals the effects of catcalling in the form of anxiety, decreased self-esteem, self-objectification, and restrictions on women's mobility. The integration of these three perspectives shows that catcalling contradicts the basic Qur'anic values of justice, honor, and social security. This study emphasizes that preventing catcalling requires a holistic approach through Qur'anic values-based education, deconstruction of patriarchal culture, and strengthening public regulations to make social spaces safer, more equitable, and dignified for all individuals.